1993
DOI: 10.1161/01.cir.88.4.1826
|View full text |Cite
|
Sign up to set email alerts
|

Cellular electrophysiological effects of hyperthermia on isolated guinea pig papillary muscle. Implications for catheter ablation.

Abstract: Hyperthermia causes significant changes in myocardial cellular electrophysiological properties that include membrane depolarization, reversible and irreversible loss of excitability, and abnormal automaticity. There appear to be specific temperature ranges for reversible and irreversible electrophysiological changes. These observations may have important implications for tissue temperature monitoring during radiofrequency catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
0
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(159 citation statements)
references
References 11 publications
11
144
0
4
Order By: Relevance
“…Previous reports have demonstrated that irreversible electrophysiologic changes to myocytes occur early at 50°C. 26 Because only 1 ablation Ͼ55°C did not result in a transmural lesion, these data suggest that the target tissue temperature at the PV orifice should be 55°C. Furthermore, tissue temperatures remain elevated even after termination of RF energy.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have demonstrated that irreversible electrophysiologic changes to myocytes occur early at 50°C. 26 Because only 1 ablation Ͼ55°C did not result in a transmural lesion, these data suggest that the target tissue temperature at the PV orifice should be 55°C. Furthermore, tissue temperatures remain elevated even after termination of RF energy.…”
Section: Discussionmentioning
confidence: 91%
“…The mean number of applications of RF energy per patient was 5.9±3.3 (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There were no complications except for 1 patient with transient AV block.…”
Section: Clinical Resultsmentioning
confidence: 98%
“…5 Haines and Watson reported a temperature range of 46.6-48.9°C in the marginal area between viable and nonviable tissue estimated in vitro using the right ventricle. 6 Hirao et al performed temperature monitoring catheter ablation of the AV junction in dogs and the threshold temperatures at which a transient effect and a permanent effect on AV conduction were observed were 45 and 49°C, respectively.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…16 In this event, T-wave peaking in the endocardial electrogram may have indicated nonlethal injury, with secondary tissue hyperkalemia. 33,34 The most specific repolarization change indicating visible midmyocardial coagulation was ST-segment depression (Figure 4, Table 3). However, electrogram changes were relatively insensitive to the development of intramural coagulation and are not predictive of optical fiber penetration.…”
Section: Discussionmentioning
confidence: 99%